DEVELOPMENT OF UNDERARM PASSING IN VOLLEYBALL THROUGH TRADITIONAL GAME APPROACH - Rohendi, Aep; Tangkudung, James A.P. (Program Pascasarjana Universitas Negeri Jakarta, 2015)
This research is aimed to develop a model of underarm passing in volleyball through traditional gameâs basic movement approach. The method used for this learning method development is Research and Development (R & D) Development Method. By choosing SMPN III Parongpong in West Bandung Regency as the location of this study, this study is done through 8 stages: first, determining idea to develop; second, producing a design; third, evaluating, Â improving and completing the text; forth, revising a product by the expert; fifth, a prototype Â product done by taking product picture; sixth, prototype test, the test of subject field both in stage I and stage II test; seventh, revising a second product of which revision was done by an expert; eighth, producting a complete Â to be the final product. From those stages, the result of the study is gained by first stage evaluation analysis of ten products. The total respondent score is resulted with data number = 123. Therefore, effectiveness of new teaching method in total = 123 : 144= 0,85 or 85% Â from the expected criteria and based on stage II evaluation analysis by using numbered final product, the total respondent score is resulted with data number = 246. Therefore, the total effectiveness of teaching method = 246 : 288 = 0,85 or 85% from the expected criteria to fulfill valid criteria. Based on the result of the study, it can be concluded that: (1) Underarm passing learning model in volleyball through gatrik traditional game approach in SMPN 3 Parongpong is needed by Physical Education teachers and improving the learning process of underarm passing effectively and efficiently. (2) Application of the developed learning model will make students more motivated in joining learning process.